Patient and public involvement in the development of health services: Engagement of underserved populations in a quality improvement programme for inflammatory bowel disease using a community‐based participatory approach - Elena Sheldon; Naseeb Ezaydi; Melanie Ditmore; Olga Fuseini; Rachel Ainley; Kerry Robinson; Daniel Hind; Alan J. Lobo (Wiley, 2024)
Abstract Introduction Involving people with lived experience is fundamental to healthcare development and delivery. This is especially true for inflammatory bowel disease (IBD) services, where holistic and personalised models of care are becoming increasingly important. There is, however, a significant lack of representation of underserved and diverse groups in IBD research, and there are significant barriers to healthcare access and utilisation among minority groups in IBD. IBD centres need to be aware of these experiences to address barriers via service changes, improve interactions with local communities and promote meaningful engagement for improved health outcomes. Methods A pragmatic community‐based approach was taken to engage with leaders and members of underserved groups across 11 workshops representing Roma, Afro‐Caribbean, people of African descent and the wider black, Asian and minority ethnic (BAME) communities, Muslim women, refugee community members, deprived areas of South Yorkshire, LGBTQ+ and deaf populations. Thematic analysis of field notes identified patterns of attention across the community groups and where improvements to services were most frequently suggested. Results Findings demonstrated several barriers experienced to healthcare access and utilisation, including language accessibility, staff attitudes and awareness, mental health and stigma, continuity of support, and practical factors such as ease of service use and safe spaces. These barriers acted as a lever to co‐producing service changes that are responsive to the health and social care needs of these groups. Conclusions Engaging with people from a range of communities is imperative for ensuring that service improvements in IBD are accessible and representative of individual needs and values. Patient or Public Contribution Local community leaders and members of community groups actively participated in the co‐design and development of improvements to the IBD service for a local hospital. Their contributions further informed a pilot process for quality improvement programmes in IBD centres.